Challenges of Multiculturalism: Integration of Religion in State Policy - Annisa, Neng Nur; Tabassum, Nabila (FISIP UIN Sunan Gunung Djati Bandung, 2023)
Research Problem: This abstract addresses the intricate challenges posed by the integration of religion in state policy within multicultural societies. It focuses on the tensions that arise when religious beliefs intersect with the principles of secular governance, highlighting the dilemmas faced by governments in striking a balance between respecting religious freedom and upholding the separation of religion and state. Research Purposes: The primary purpose of this abstract is to examine the complexities surrounding the incorporation of religion into the framework of state governance. It aims to shed light on the diverse approaches taken by governments to address these challenges and the potential implications for social cohesion, individual rights, and democratic governance. Research Methods: Methodologically, this abstract draws upon case studies from various countries to explore the integration of religion in state policy. It employs a qualitative analysis approach to delve into the tensions and dilemmas faced by governments in multicultural societies when dealing with issues related to religious freedom and secular governance. Results and Discussion: The abstract discusses the multifaceted issues surrounding the integration of religion in state policy, highlighting the diverse approaches taken by governments to address these challenges. It examines the potential implications for social cohesion, individual rights, and democratic governance, while also exploring the role of dialogue, education, and policy-making in mitigating these challenges. Research Implications and Contributions: This abstract provides a comprehensive overview of the challenges posed by the integration of religion in state policy within multicultural societies. It invites further research and discussion on this critical aspect of multiculturalism, aiming to contribute to a deeper understanding of the complexities surrounding the relationship between religion, governance, and societal cohesion.